2015
DOI: 10.1039/c5cp04475h
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of local molecular motions of aromatic sidechains in proteins by 2D and 3D fast MAS NMR spectroscopy and quantum mechanical calculations

Abstract: We report a new multidimensional magic angle spinning NMR methodology, which provides an accurate and detailed probe of molecular motions occurring on timescales of nano- to microseconds, in sidechains of proteins. The approach is based on a 3D CPVC-RFDR correlation experiment recorded under fast MAS conditions (νR = 62 kHz), where 13C-1H CPVC dipolar lineshapes are recorded in a chemical shift resolved manner. The power of the technique is demonstrated in model tripeptide Tyr-(D)Ala-Phe and two nanocrystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 56 publications
0
53
0
2
Order By: Relevance
“…1 H- 13 C dipolar parameters can be conveniently measured in a 3D experiment, where the dipolar recoupling period is followed by a 13 C- 13 C mixing step, such as fpRFDR, as reported previously 32 and shown in Figure 1c in the context of wPARS recoupling sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 H- 13 C dipolar parameters can be conveniently measured in a 3D experiment, where the dipolar recoupling period is followed by a 13 C- 13 C mixing step, such as fpRFDR, as reported previously 32 and shown in Figure 1c in the context of wPARS recoupling sequence.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates that the fpRFDR mixing does not introduce any artifacts into the spectra, in accord with the previous findings for a 3D CPVC-RFDR experiment. 32 …”
Section: Resultsmentioning
confidence: 99%
“…The evidence of such dynamics under non-DNP conditions has been recently reported for aromatic sidechains. 63-67 In principle, analysis of the conformational space and the populations could provide a glimpse into the type of motions that exist. However, data at variable temperatures will be required for a quantitative analysis of such dynamics, which can depend on motional timescales, amplitudes, populations and potential energy barriers.…”
Section: Resultsmentioning
confidence: 99%
“…109,110,111,112,113,114 Its fast MAS variant allows to add 1 H-13 C dipolar dimensions in multidimensional experiments 68,115,116,117,118 Recently, it was demonstrated that on-resonance CW 14 N irradiation during the CSA recoupling period with rf field ~30 times smaller than the 14 N quadrupolar couplings largely decouples 14 N-1 H interactions leading to perfect 1 H CSA lineshapes 127 .…”
Section: Sensitivitymentioning
confidence: 99%